Effect of Happiness Counseling on Depression, Anxiety, and Stress in Women with Recurrent Miscarriage - Elsharkawy NB; Mohamed SM; Awad MH; Ouda MMM (Dove Medical Press, 2021)
Nadia Bassuoni Elsharkawy,1,2 Sayeda Mohamed Mohamed,3 Mohamed Hammam Awad,4 Marwa Mohamed Ahmed Ouda1,5 1Nursing Department, College of Applied Medical Sciences, Jouf University, Sakaka, Saudi Arabia; 2Maternal and Newborn Health Nursing Department, Faculty of Nursing, Cairo University, Cairo, Egypt; 3Psychiatric Mental Health Nursing Department, Faculty of Nursing, Cairo University, Cairo, Egypt; 4Obstetrics and Gynecology Department, Faculty of Medicine, Cairo University, Cairo, Egypt; 5Pediatric Nursing Department, Faculty of Nursing, Damanhur University, EgyptCorrespondence: Nadia Bassuoni ElsharkawyNursing Department, College of Applied Medical Sciences, Jouf University, Sakaka, Jouf, Kingdom of Saudi ArabiaTel +966-554180474Email nelsharkawy@ju.edu.saPurpose: This study investigated the effectiveness of a happiness counseling program on depression, anxiety, and stress in pregnant women with a history of recurrent miscarriage.Patients and Methods: A parallel randomized controlled trial research design was used in this study, which was conducted at the high-risk inpatient unit of the Obstetrics and Gynecology Hospital of Cairo University Hospitals in Cairo, Egypt. A total of 60 pregnant women who had previously experienced multiple miscarriages were randomly assigned to intervention and control groups (n=30 each). The tools used for data collection were demographic and obstetric data questionnaires and the 21-item Depression, Anxiety, and Stress Scale (DASS-21). Happiness counseling sessions were conducted for the intervention group. Data for qualitative variables were analyzed with the chi-squared test, and the Student’s t test for paired samples was used to compare mean DASS-21 scores of the intervention and control groups. The Pearson correlation coefficient was used to analyze the association between variables.Results: The happiness counseling sessions reduced depression, anxiety, and stress in women with recurrent miscarriage, resulting in lower mean DASS-21 scores for the intervention group compared to the control group.Conclusion: The happiness counseling program had a positive effect on reducing depression, anxiety, and stress in women with recurrent miscarriage. We recommend that this program be used as an effective, low-cost, and noninvasive intervention to improve the mental health and overall wellbeing of women with recurrent miscarriage.Keywords: happiness counseling program, depression, anxiety, stress, recurrent miscarriage